The effects of two methods of reflexology and stretching exercises on the severity of restless leg syndrome among hemodialysis patients - Nahid Shahgholian; Shahrzad Khojandi Jazi; Jahangir Karimian; Mahboubeh Valiani (Wolters Kluwer Medknow Publications, 2016)
Background: Restless leg syndrome prevalence is high among the patients undergoing hemodialysis. Due to several side effects of medicational treatments, the patients prefer non-medicational methods. Therefore, the present study aimed to investigate the effects of two methods of reflexology and stretching exercises on the severity of restless leg syndrome among patients undergoing hemodialysis. Materials and Methods: This study is a randomized clinical trial that was done on 90 qualified patients undergoing hemodialysis in selected hospitals of Isfahan, who were diagnosed with restless leg syndrome through standard restless leg syndrome questionnaire. They were randomly assigned by random number table to three groups: Reflexology, stretching exercises, and control groups through random allocation. Foot reflexology and stretching exercises were conducted three times a week for 30-40 min within straight 4 weeks. Data analysis was performed by SPSS version 18 using descriptive and inferential statistical analyses [one-way analysis of variance (ANOVA), paired t-test, and least significant difference (LSD) post hoc test]. Results: There was a significant difference in the mean scores of restless leg syndrome severity between reflexology and stretching exercises groups, compared to control (P < 0.001), but there was no significant difference between the two study groups (P < 0.001). Changes in the mean score of restless leg syndrome severity were significantly higher in reflexology and stretching exercises groups compared to the control group (P < 0.001), but it showed no significant difference between reflexology massage and stretching exercises groups. Conclusions: Our obtained results showed that reflexology and stretching exercises can reduce the severity of restless leg syndrome. These two methods of treatment are recommended to the patients.